2017
DOI: 10.1002/ijc.30859
|View full text |Cite
|
Sign up to set email alerts
|

Gene–environment interactions involving functional variants: Results from the Breast Cancer Association Consortium

Abstract: Investigating the most likely causal variants identified by fine‐mapping analyses may improve the power to detect gene–environment interactions. We assessed the interplay between 70 single nucleotide polymorphisms identified by genetic fine‐scale mapping of susceptibility loci and 11 epidemiological breast cancer risk factors in relation to breast cancer. Analyses were conducted on up to 58,573 subjects (26,968 cases and 31,605 controls) from the Breast Cancer Association Consortium, in one of the largest stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
0
19
0
3
Order By: Relevance
“…Increased risk of breast cancer with smoking has also been seen in some [ 40 , 41 ], but not all ( see review [ 1 ] and a large meta-analysis [ 41 ]), studies of BRCA1/2 carriers (or by proxy, women with three or more first-degree relatives with breast or ovarian cancer [ 42 ]). There are also reports of significant interactions with smoking and polymorphisms in carcinogen metabolism genes NAT2 [ 43 ] and CYP1A1 [ 44 , 45 ] as well as breast cancer susceptibility single-nucleotide polymorphisms [ 46 , 47 ]. Moreover, BRCA1 and BRCA2 proteins are involved in the repair of DNA damage, and it is therefore possible that BRCA1/2 carriers may be more sensitive to effects of carcinogens in cigarette smoke.…”
Section: Discussionmentioning
confidence: 99%
“…Increased risk of breast cancer with smoking has also been seen in some [ 40 , 41 ], but not all ( see review [ 1 ] and a large meta-analysis [ 41 ]), studies of BRCA1/2 carriers (or by proxy, women with three or more first-degree relatives with breast or ovarian cancer [ 42 ]). There are also reports of significant interactions with smoking and polymorphisms in carcinogen metabolism genes NAT2 [ 43 ] and CYP1A1 [ 44 , 45 ] as well as breast cancer susceptibility single-nucleotide polymorphisms [ 46 , 47 ]. Moreover, BRCA1 and BRCA2 proteins are involved in the repair of DNA damage, and it is therefore possible that BRCA1/2 carriers may be more sensitive to effects of carcinogens in cigarette smoke.…”
Section: Discussionmentioning
confidence: 99%
“…Dennoch ist der Einsatz der genetischen und nichtgenetischen Risikoinformation so weit fortgeschritten wie nie zuvor. Es existieren einige Arbeiten, die versuchen, auf der einen Seite die Gen-Gen-Interaktion und auf der anderen Seite die Gen-Umwelt-Interaktion zu entschlüsseln [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Die Analysen, die am ehesten in der Praxis für Patientinnen eingesetzt werden können, betreffen die Nutzung möglichst vieler Risikovarianten, um mit ihnen Risikogruppen für Patientinnen zu definieren [24,[30][31][32].…”
Section: Prävention Und Risikofaktorenunclassified
“…Studies focusing on susceptibility variants identified in GWAS on breast cancer, 58,59 have reported a significant interaction of smoking status with rs7558475 in CFLAR (CASP8 and FADD-like apoptosis regulator). 59 As already mentioned, other studies have concluded that cigarette smoking is associated with increased breast cancer risk among women with NAT2 slow acetylation genotypes, 33 but results have been heterogeneous. However, none of these studies has considered the combined effect of tobacco smoking with genetic variations using a gene-set approach.…”
Section: Tobacco Smoking and Genetic Variationmentioning
confidence: 99%